The Pharmaceutical Industry and Dependency in the Third World - Gereffi, Gary (Book collections on Project MUSE., 2017)
Gary Gereffi first explains how foreign corporations took over the flourishing Mexican steroid industry in the 1950s and 1960s and thwarted the country's later attempts to establish a more equitable distribution of industry benefits. In this valuable theoretical contribution Professor Gereffi uses the Mexican industry's plight as a crucial-case test for dependency theoryOriginally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.